PENGARUH TINGKAT SUKU BUNGA, PROMOSI, DAN KINERJA KARYAWAN TERHADAP MINAT PEMINJAMAN NASABAH PADA PT ALCO DANA MANDIRI - Sianipar, Rosalyn; Asron Saputra, S.E., M.Si. (LPPM Universitas Putera Batam, 2022)
ABSTRACTThis study aims to identify the effect of interest rates, promotion, and performance, towards customers interest on loaning at PT Alco Dana Mandiri Batam. Population in this study are customers at PT Alco Dana Mandiri per year totaling 756 customer per 6 months calculation, and using a sample of 260 people. This research was conducted using the Random Sampling technique. technique used in this research consist in descriptive test, test of vailidty, reability test, test of normality, multicolinear test, heterocedasity test and using multiple linear regression test, determination test, t test and f test. The results of this study are that the calculated F value is 65.972 which is way higher than the f that show up in table which valued at 2.417 also the significance value in sig. resulting 0 value which is least than 0.05, therefore there is a simultaneous effect formed by all independent variables that consists of interest rates, promotion and performance.Keywords: consumer interest in loan;interest rates; performances; promotion.